Incidence and All-Cause Mortality Rates in Neonates Infected With Carbapenem Resistant Organisms - Thomas, Reenu; Ondongo-Ezhet, Claude; Motsoaledi, Nini; Sharland, Mike; Clements, Michelle; Velaphi, Sithembiso (Frontiers in Tropical Diseases, 2022)
Introduction Multidrug-resistant, Gram-negative infections, particularly due to carbapenem resistant organisms (CRO), have increased globally. Few studies have reported on the burden of CRO in neonates from low-middle income countries (LMIC). This study aimed to determine the incidence and mortality rates of culture-confirmed Gram-negative infections, with a special focus on CRO in a neonatal unit from a LMIC. Materials and Methods Positive bacterial cultures from sterile sites of infants admitted in the neonatal unit from the 1st January 2018 to 31st December 2019, were reviewed retrospectively. Type of organism, susceptibility and outcomes were recorded. Data on Gram-negative isolates, including the CRO, were extracted. Rates and outcomes were analysed. Results There were 2219 neonates with organisms isolated from sterile sites (blood and cerebrospinal fluid), accounting for 30% of all admissions, giving a neonatal sepsis incidence of 17.9/1000 patient-days. There was a total of 1746 positive isolates (excluding coagulase negative Staphyloccocus). Of these, 1706 (98%) were isolated from blood, and 40 (2%) from cerebrospinal fluid. Overall, 1188 (68%) were Gram-negative, 371 (21%) Gram-positive and 187 (10.7%) fungal isolates. The common Gram-negatives were Acinetobacter baumannii (526/1188;44%) and Klebsiella pneumoniae (469/1188;40%). Carbapenem resistance was observed in 359 (68%) of the Acinetobacter baumannii (CRAB) and in 103 (18%) of the Enterobacterales (CRE) isolates, with 98% of CRE being Klebsiella pneumoniae (CR-Klebs). Twenty-four (41%) of Pseudomonas species were carbapenem resistant. Overall, carbapenem resistance was seen in 42% of all Gram-negative organisms. The rate of CRAB and CRE were 2.9 and 0.8/1000 patient-days respectively. The overall, all-cause in-hospital mortality rate in infants with Gram-negative isolates was 22%, with higher mortality rate in those infected with CRO compared to non-CRO (34% vs 13%; OR 3.44; 95% CI 2.58–4.60; p < 0.001). The mortality rate in infants with CRE was higher than those with CRAB (48% vs 33%; OR 1.85; 95% CI 1.18–2.89; p = 0.007). Conclusion We observed a high incidence of positive cultures from sterile sites. The common organisms isolated were Gram-negatives, and among these carbapenem resistance was high and was associated with high mortality. Mortality was higher in infants with CRE compared to those with CRAB.